Evidence-based guidelines for treating bipolar disorder: recommendations from the British Association for Psychopharmacology. - Goodwin, G (2003)
The British Association for Psychopharmacology guidelines specify the scope and target of treatment for bipolar disorder. They are based explicitly on the available evidence and presented, similar to previous Clinical Practice guidelines, as recommendations to aid clinical decision-making for practitioners. They may also serve as a source of information for patients and carers. The recommendations are presented together with a more detailed review of the available evidence. A consensus meeting, involving experts in bipolar disorder and its treatment, reviewed key areas and considered the strength of evidence and clinical implications. The guidelines were drawn up after extensive feedback from participants and interested parties. The strength of supporting evidence was rated. The guidelines cover the diagnosis of bipolar disorder, clinical management and strategies for the use of medicines in short-term treatment of episodes, relapse prevention and stopping treatment.